Hugh Llewellyn Keenleyside: Commissioner of the Northwest Territories, 1947-1950 - Grant, Shelagh D. (ARCTIC, 1990)
In March 1947, Hugh Keenleyside was recalled from his posting as Ambassador to Mexico and appointed Commissioner of the Northwest Territories and Deputy Minister of Mines and Resources, positions he held until October 1950. His credentials were unusual and his tenure short, but within three and a half years, the former diplomat transformed the somewhat laissez-faire style of northern government into one of active intervention supported by major financial investment. . Hugh Keenleyside's accomplishments as Commissioner of the Northwest Territories cannot be fully understood without recognizing that he had failed to meet his own expectations and ambitious objectives. Yet regardless of resistance and criticism from his more conservative colleagues and political masters, the determined reformer dramatically changed the direction of government policies to end the period of "benign neglect" and mark the beginning of heavy financial investment and government intervention into almost every aspect of northern affairs. .